Both de-growth and a-growth to achieve strong and weak sustainability: a theoretical model, empirical results, and some ethical insights - Zagonari, Fabio (Frontiers in Sustainability, 2024)
This paper conceptually characterises and theoretically represents the four main sustainability paradigms (strong sustainability, weak sustainability, de-growth, a-growth) in terms of equalities and inequalities. It then applies these conditions to developed and less-developed countries (OECD and non-OECD countries) and empirically shows that the change in production technology (∆θ) required by a-growth is impossible and the change in consumption preferences (∆α) required by degrowth is unfeasible. Finally, it combines a-growth and de-growth in a theoretical solution for the relationship between ∆α and ∆θ that meets the conditions required by both strong and weak sustainability (parameters are the world's population, consumption preferences and production technologies or concerns for nature and future generations in developed and less-developed countries) and empirically demonstrates that this solution is feasible. In particular, sustainability turns out to be an ethical issue more than a technological issue and the ethical concern for nature turns out to be more favorable than the ethical concern for future generations. Ethical assumptions and implications of the four main sustainability paradigms are highlighted as well as ethical assumptions and implications of the combined theoretical model are discussed. In particular, intergenerational efficiency is achieved in terms of welfare and intergenerational equity is achieved in terms of the environmental status.